(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The paper describes in detail the biochemical analysis of antimicrobial peptides in the oral cavity, which provide the first line of defense of oral tissues from the introduction of pathogenic factors. Several groups of antimicrobial peptides have been found in the oral cavity, which have different origins and are active against bacteria, fungi and viruses, as well as having the properties of immunomodulators and chemoattractants. Antimicrobial peptides play a critical role in maintaining oral health.